SYNTHESIZE OF TiO2 NANOPARTICLES BY PLANETARY BALL MILL FOR DYE-SENSITIZED SOLAR CELLS (DSSC) PHOTOELECTRODE APPLICATION - Nurlaela, Ai; Yuniarti, Elvan; Saptari, Siti Ahmiatri (Program Studi Fisika Universitas Negeri Jakarta, 2023)
In this study, the production of TiO2 nanoparticles from microcrystalline powder was accomplished using the high-energy ball milling (HEBM) technique. Three samples were milled for 0.5, 1, and 1.5 hours. The unmilled powder was also characterized as a comparison. The X-ray diffraction (XRD) technique was utilized to investigate the changes in the microstructure of the milled powders over time. The XRD curve of milled samples showed the broadening of the diffraction peaks, which indicates a decrease in particle size after the milling process. Using the Debye–Scherrer relation, obtain the particle size that decreased from 138.43 nm before milled to 76.65 nm after 0.5 hours milled, 90.63 nm after 1 hour milled, and 83.05 nm after 1.5 hours milled. XRD analysis also showed that TiO2 was in an anatase phase before and after milling. Furthermore, two samples of TiO2, unmilled and after 0.5 hours milled, were used as a working photoelectrode of DSSC with dye from mustard leaves. DSSC efficiency was measured with a 1000-watt halogen lamp. The efficiency of DSSC with photoelectrodes using TiO2 after 0.5 hours milled, which is 0.1715, was higher than using TiO2 before milled, which is 0,0987. The Large surface area in TiO2 enhances the efficiency of DSSC, indicating that the HEBM technique is quite suitable for producing these nanoparticles for this aim.